A conserved RNA structural motif for organizing topology within picornaviral internal ribosome entry sites - Deepak Koirala (Nature Portfolio, 2019)
Picornaviruses use modular RNA domains in their internal ribosome entry sites (IRESs) for translation through non-canonical, cap-independent mechanisms. Here the authors report the crystal structure of domain V from the IRES of hepatitis A virus (HAV) ssRNA genome, suggesting that the functional homology among different types of picornaviral IRESs is structure-based.